2021
DOI: 10.1007/978-3-030-73988-1_25
|View full text |Cite
|
Sign up to set email alerts
|

Shifting to Emergency Remote Teaching Due to the COVID-19 Pandemic: An Investigation of Greek Teachers’ Beliefs and Experiences

Abstract: During schools' closure, due to the pandemic of COVID-19, teachers around the globe were forced to transfer their instruction on-line. They were facing a range of barriers and difficulties to plan and provide online remote teaching to their students. This paper reports on a study exploring Greek primary and secondary education teachers' views about emergency remote teaching and elearning. The survey conducted in May 2020, just after schools' reopening in Greece. A total of 694 K-12 teachers responded to an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…By contrast, their relationships with colleagues were neutral and their relationships with students and parents slightly negative. These findings confirm the findings reported by similar studies conducted in Greece which concluded that Greek teachers had managed to respond successfully to the challenge of delivering their courses through asynchronous and synchronous modes but, at the same time, without maintaining the envisaged relationships with colleagues and students (Jimoyiannis et al, 2021;Nikiforos et al, 2020).…”
Section: Correlational and Regression Analysessupporting
confidence: 90%
See 2 more Smart Citations
“…By contrast, their relationships with colleagues were neutral and their relationships with students and parents slightly negative. These findings confirm the findings reported by similar studies conducted in Greece which concluded that Greek teachers had managed to respond successfully to the challenge of delivering their courses through asynchronous and synchronous modes but, at the same time, without maintaining the envisaged relationships with colleagues and students (Jimoyiannis et al, 2021;Nikiforos et al, 2020).…”
Section: Correlational and Regression Analysessupporting
confidence: 90%
“…At a later stage, they adopted synchronous forms of distance teaching with technical problems such as limited resources, limited support for children at home and limited experience of using information communication technology emerging as important obstacles to overcome (Nikolopoulou, 2022 ). Similar results were reported by studies on the practices of primary and secondary school teachers; despite struggling initially with implementing distance education, they subsequently rose to the challenge of catering effectively for their students (Jimoyiannis et al, 2021 ; Nikiforos et al, 2020 ). Moreover, these studies highlighted the teachers' perceived needs for professional development and support.…”
Section: Teachers' Resilience During Covid‐19supporting
confidence: 73%
See 1 more Smart Citation
“…In the case of domestic resources, it can be seen that the majority of educators who use emerging strategies make use of these, unlike those who use traditional strategies. These findings are related to the idea that educators had to go beyond the curricula and reorient content to students' homes to maximize understanding [50]. Likewise, this idea of reinterpreting the home as a type of educational context revisits the idea of selfdirected learning in which students focus on their situational experience for learning with concrete materials.…”
Section: Comparison Of Didactic Strategies According To the Type Of E...mentioning
confidence: 91%
“…Therefore, these two teaching conditions cannot be identified as one and the same. Thus, many researchers point out that it is better to use the term «emergency distance teaching» (Jimoyiannis, Koukis & Tsiotakis, 2021).…”
Section: Introductionmentioning
confidence: 99%